HCC masquerading as gluteal mass: A rare presentation (Indian Journal of Case Reports, 2024)
Hepatocellular carcinoma (HCC) is the most common primary tumor of the liver. Extrahepatic metastasis occurs mostly through the hematogenous route and is seen in around one-third of patients with the common sites of involvement being the lungs, regional lymph nodes, bone, adrenal glands, and pancreas. Soft-tissue metastasis from HCC is an extremely rare condition. Here, we present a rare case of an elderly male, with HCC presenting as a soft-tissue mass in the gluteal region. We further provide a detailed discussion regarding the investigative approach used to arrive at the diagnosis and the treatment modalities offered. Case reports like this may offer insight into the possibilities of such unusual presentations and aid the clinician in his endeavor to the early diagnose and treat the patient.